MENGEKSPLORASI NILAI-NILAI BUDAYA TEMBANG SUNDA CIANJURAN (EXPLORING THE CULTURAL VALUES TEMBANG SUNDA CIANJURAN - Aprilla Adawiyah Mia Fatimatul Munsi (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2018)
AbstractExploring The Cultural Values Tembang Sunda Cianjuran.. Tembang Sunda Cianjuran is a typicalCianjur song that has the values of life in it. This research includes descriptive analytic research thataims to describe the cultural values of Tembang Sunda Ciajuran and its function for the community. Theinstrument of this research is five tembang Sunda Cianjuran. The text is for obtaining cultural valuesdata. Meanwhile, to analyze the function of Tembang Sunda Cianjuran for the community, the dataobtained from the interview. Problems related to the nature of human positions in space and time is themost dominant problem that is oriented to the past. Tembang Sunda Cianjuran originally served as anadvice or reminder about the teachings of Islam for the servants in the Hall, but now its function has beenextended to all levels of society. The contents of the song also varied, not only about religious teachingsbut varied. For example about nature, culture, and others. So, Tembang Sunda Cianjuran should bepreserved by the next generation so as not to be eroded by the times.Key words: cultural value, Tembang Sunda CianjurAbstrakMengeksplorasi Nilai-Nilai Budaya Tembang Sunda Cianjuran. Tembang Sunda Cianjuranmerupakan tembang khas Cianjur yang memiliki nilai-nilai kehidupan di dalamnya. Penelitianini termasuk penelitian deskriftif analitik yang bertujuan untuk mendeskripsikan nilai-nilai budayaTembang Sunda Ciajuran. Instrumen penelitian ini berupa lima buah teks Tembang Sunda Cianjuran.Teks tersebut untuk memperoleh data nilai-nilai budaya. Permasalahan yang berkaitan dengan hakikatdari kedudukan manusia dalam ruang dan waktu adalah permasalahan yang paling dominan yaituberorientasi ke masa lalu.Tembang Sunda Cianjuran pada mulanya berfungsi sebagai nasihat ataupengingat tentang ajaran Islam untuk para abdi di Pendopo, tetapi sekarang fungsinya sudah meluaskepada semua lapisan masyarakat. Isi dari tembangnya pun beragam, tidak hanya tentang ajaranagama. Misalnya tentang alam, budaya, dan lain-lain. Jadi, hendaknya Tembang Sunda Cianjurandapat dilestarikan oleh para generasi penerus agar tidak tergerus oleh zaman.Kata-kata kunci: nilai budaya, Tembang Sunda Cianjur